THE VALUE OF THE INSTRUMENT DOMBRA PLAYING BY PUPILS IN A GROUP - Amirkhamzin, N.K.; Akbuzhurova, S.Zh.; Esmaganbetova, Sh.K. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
In this article is discussed the importance of group playing on the dombra of students in dombra clubs at school or in music studios. Several pedagogical repertoires for pupils are also considered. The educational side of dombra art is told.
Keywords: music; pupils; pedagogical repertoire; dombra; spiritual wealth